Tomorrow's biofuels: Goals and hopes. Issue 7 (3rd April 2017) - Demirbas, Ayhan
ABSTRACT: The aim of the present study is to investigate the importance of biofuels in the near future. A large number of research projects in the field of biofuels have been carried out. Biomasses can be converted into primarily liquid products in the presence of a reducing reagent, e.g., carbon monoxide or hydrogen. The main biofuels from biomasses are bioethanol, biodiesel, biohydrogen, biogas, and charcoal. The main biofuels are bioethanol, biobutanol, biodiesel, vegetable oils, biomethanol, pyrolysis oils, biogas, synthesis gas, and biohydrogen. The two major ethanol producers are the United States and Brazil followed by the European Union and China. The two major biodiesel producers are the European Union and Indonesia followed by Brazil and the United States. While the share of biofuels will become 5.0% the total automotive fuel consumption in 2020, it will increase to 11.8% in 2050. Liquid biofuels, especially ethanol and biodiesel, hold promise for the future. There is a worldwide interest in sustainable energy sources based on biofuels. Liquid biofuels are important alternative to fossil liquid fuels such as gasoline and diesel fuel. Biofuels are promising alternatives for the road, aviation, and maritime fueling. Suitable liquid biofuels can be used as bio-jet fuels, and the alternative biofuels of today may become the conventional fuels in the future.